Fighting cartels: some economics of council regulation (EC) 1/2003 - Birgit E. Will; Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2008)
This paper investigates the effectiveness of the new Council Regulation (EC) 1/2003 which replaces the mandatory notification and authorization system by a legal exception system. Effectiveness is operationalized via the two subcriteria compliance to Art. 81 EC Treaty and the probabilities of type I and type II errors committed by the European Commission. We identify four different types of Perfect Bayesian Nash Equilibria: fullcompliance, zero-compliance, positive-compliance and full-deterrence. We show that the Commission can, in principle, hit the full-compliance equilibrium, where the cartelizing firms fully obey the requirements of Art 81(3) EC Treaty and both error probabilities are zero.
Keywords: K21; K42; L40; 330; competition law; cartel law enforcement; legal exception; imperfect